2018
DOI: 10.1108/he-02-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health literacy among school-aged children

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
3
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 37 publications
6
78
3
13
Order By: Relevance
“…A probable explanation for this is that the HLSAC instrument caused a ceiling effect. According to cut points proposed, the sample and subgroup HL mean scores were medium and close to high [13,31]. This could also be caused by the age range of the present sample.…”
Section: Plos Onementioning
confidence: 57%
“…A probable explanation for this is that the HLSAC instrument caused a ceiling effect. According to cut points proposed, the sample and subgroup HL mean scores were medium and close to high [13,31]. This could also be caused by the age range of the present sample.…”
Section: Plos Onementioning
confidence: 57%
“…Compared to adult health literacy, evidence on children and adolescents' health literacy is rather limited. The Finnish data from the Health Behavior in School-aged Children survey (HBSC) shows that 1/3 of the 7th and 9th graders had high levels of health literacy and around 60% had shown moderate levels [10]. The HBSC results for Lithuania show high levels of health literacy in 17.4% of the children, while 70.5% were found to have moderate levels [11].…”
Section: Introductionmentioning
confidence: 99%
“…A school-based survey on health literacy in 6th graders in Taiwan found that 44% of the children had high levels of health literacy (high: 16.3%; very high: 27.7%), while 56% had low health literacy (very low: 26.6%; low: 29.5%) [12]. In the past, studies have also shown that higher levels of health literacy are associated with better health behaviors in adolescents [13], that higher health literacy in school-aged children is associated with increased health outcomes [10,12] and that higher levels of health literacy have an impact of physical activity and self-reported health in adolescents [14].…”
Section: Introductionmentioning
confidence: 99%
“…and apply health information in order to make judgments and take decisions in everyday life" (Sørensen et al, 2012, p. 3). A number of explanations have been developed that describe the constructs and variables that either predict health literacy rates (Berkman, Sheridan, Donahue, Halpern, & Crotty, 2011) or describe the outcomes associated with the level of health literacy in a population [e.g., those living with diabetes (Schillinger et al, 2002), cancer (Morris et al, 2013), or children and young people (e.g., Paakkari, Torppa, Villberg, Kannas, & Paakkari, 2018;Parisod, Axelin, Smed, & Salanterä, 2016)]. An early analysis of the health literacy concept (Speros, 2005) described the defining attributes of health literacy as reading and numeracy skills, comprehension, the capacity to use information in health care decisionmaking, and successful functioning as a health care consumer including navigating health care systems.…”
mentioning
confidence: 99%